2005
DOI: 10.1210/jc.2005-0272
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Wnt5b Gene in Leiomyoma Cells: Implications for a Role of the Wnt Signaling Pathway in the Uterine Benign Tumor

Abstract: Specific Wnt signaling genes are overexpressed in leiomyoma cells. Moreover, in these cells, the regulation of Wnt5b expression by retinoids appears to be attenuated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 24 publications
0
25
0
2
Order By: Relevance
“…Another association was identified among genetic variants of rs2784917, gene expression of WNT5B, and etoposide IC 50 in the YRI. WNT signaling pathway plays a key role in carcinogenesis and embryogenesis and has been found to be up-regulated in gastric, esophageal, pancreatic, breast cancer cell line, and uterine leiomyoma cells (25,26). Our study showed that the TT genotype of SNP rs2784917 was associated with higher WNT5B gene expression and greater sensitivity to etoposide.…”
Section: Discussionmentioning
confidence: 51%
“…Another association was identified among genetic variants of rs2784917, gene expression of WNT5B, and etoposide IC 50 in the YRI. WNT signaling pathway plays a key role in carcinogenesis and embryogenesis and has been found to be up-regulated in gastric, esophageal, pancreatic, breast cancer cell line, and uterine leiomyoma cells (25,26). Our study showed that the TT genotype of SNP rs2784917 was associated with higher WNT5B gene expression and greater sensitivity to etoposide.…”
Section: Discussionmentioning
confidence: 51%
“…Leiomyomas cells in culture have high levels of both transcripts of WNT5B and of secreted frizzled related protein 1 (SFRP1), a modulator of Wnt signaling (Mangioni et al 2005). Strong SFRP1 expression under high estrogenic conditions seems to contribute to the development of human uterine leiomyomas through the antiapoptotic effect of SFRP1 (Fukuhara et al 2002).…”
Section: Wnt Signalling Pathwaymentioning
confidence: 99%
“…The molecular causes of the disease remain unknown [1][2][3][4][5][11][12][13][14] . A variety of techniques, including differential hybridization, differential display PCR, representational difference analysis, suppression subtractive hybridization (SSH), and gene array, have been used to identify the genes whose expression is selectively altered in uterine leiomyoma [1][2][3][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…So it is very important to explore the molecular mechanism of the cause of uterine leiomyoma at protein level by studying the differential proteins between uterine leiomyoma and normal myometrium. Previous studies examining changes in protein expression in uterine leiomyoma have mainly targeted specific proteins [4,15] . To our knowledge, there is no report in which two-dimensional electrophoresis was employed to study global protein changes in uterine leiomyoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation